An Analysis of Classroom Management and Student Performance during Project-Based Learning - Sholiha, Abidatus; Jati, Sigit Pramono; Hindun (ICONELT, 2024)
This research aims to explore the implementation of project-based learning focusing on classroom management and student performance. In this study, the researcher used a qualitative design, and the data collection techniques were observation, interview, and project results. The supporting data includes photos and videos taken during the teacher’s instruction in the classroom and when the students are doing the project. The subjects are seventh-grade students at MTsN 4 Jombang academic year 2023/2024, which consists of 27 students. The results show that classroom management during the implementation of PjBL can increase the class activeness of fellow students, and the teacher also takes action in the implementation process, such as grouping students, arranging circular seating to support collaboration, adequate time management, and classroom order to remain conducive. The project results produced by the students showed interesting creativity with its own appeal with creativity. The organization and ideas of the students also showed creative thinking skills and high engagement.